Keefektifan Model Pembelajaran Creative Problem Solving (CPS) Terhadap Prestasi Belajar Matematika Smp Negeri 3 Ngabang - Permata, Jeliana Intan (Pendidikan Matematika Universitas PGRI Yogyakarta, 2019)
AbstractMathematics learning in SMP Negeri 3 Ngabang is still not optimal. The problem experienced is the lack of student involvement in the learning process. this is also related to the selection of inappropriate learning models. This affects the low student achievement. The purpose of this study was to determine the effectiveness of Creative Problem Solving (CPS) learning model on student mathematics learning achievement. The research method used is a quantitative method with comparative studies. The prerequisite test carried out normality test and homogeneity test. Hypothesis testing using the t-test. The results of the study show that the model CPS learning is effective against mathematics learning achievement compared to direct learning models. The results of the final data analysis showed the proportion of experimental class students had reached individual KKM with the results of tcount> ttable or 5.64> 1.68 Based on the average difference test obtained tcount= 1.751> 1.67 = t table and = 5%.Â Keywords: learning, learning achievement.